The influence of financial leverage and deferred tax on tax aggressiveness in telecommunications sub-sector infrastructure companies listed on the bei in 2019-2022 - Ledy Alemita Br Tarigan; Lenita Waty (Institute of Computer Science (IOCS), 2023)
This research aims to explore the impact of Financial Leverage and Deferred Tax on the level of tax aggressiveness in infrastructure companies in the Telecommunications sub-sector. This research uses quantitative descriptive methods and collects secondary data from companies listed on the Indonesia Stock Exchange in the 2019-2022 period. Sampling was carried out using the purposive sampling method. Data analysis includes descriptive statistical techniques, correlation coefficients, coefficients of determination, multiple linear regression, as well as significance tests and classical assumptions which are analyzed using Statistical Product and Solutions (SPSS) 23. The results of the study show that Financial Leverage and Deferred Taxes together have no effect. significant to the level of tax aggressiveness, with a significance value of (0.810 > 0.05). And when explained separately, financial leverage also does not have a significant influence on the level of tax aggressiveness (0.363 > 0.05). Likewise with Deferred Tax which has a significant value (0.783 > 0.05).